Association between enteral macronutrient delivery and inflammatory response in critically ill children. Issue 5 (October 2019) - Zaher, Sara; White, Deborah; Ridout, Jenna; Valla, Frederic; Branco, Ricardo; Meyer, Rosan; Pathan, Nazima
Abstract: Background and aims: An important goal of nutrition support in paediatric critical illness is minimising catabolism. While focussing on providing full energy requirements, macronutrient balance is often neglected. Studies suggest that there is interplay between nutrition and inflammation. We aimed to assess the amount of enteral macronutrients delivered compared to estimated requirements, and the association between delivered macronutrients and systemic inflammation in critically ill children. Method: We prospectively evaluated energy and macronutrient intake in critically ill children who required at least 72 h of mechanical ventilation. Data on enteral energy and macronutrient intake was collected and expressed as a percentage of the estimated requirements. Circulating levels of inflammatory cytokines were measured by ELISA and association assessed with delivery of macronutrients from the previous 24 h. Results: A total of 87 children (0–16 years) were included in this study. By day 3 the median (IQR) intake of energy, fat, carbohydrate (CHO) and protein were 75% (50–103), 85% (43–120), 63% (42–102) and 45% (23–65) respectively. We have also shown that delivery of enteral fat and protein was associated with elevation in the levels of tumour necrosis factor alpha (TNF-α) and interleukin-6 (IL-6). Conclusion: The inflammatory response in critically ill children is influenced by the amount of enteral fat and protein delivered. Our data suggests that within the feed delivered, fat is often higher than protein and CHO. It is crucial to take into account the proportion of macronutrients required and not only aim to achieve the energy goal.